Perceptions of Patient-Centered Care at Dr. M. Djamil General Hospital - Dorisnita, Dorisnita; alfitri, alfitri; Yauma, Fithratil (Frontiers on Healthcare Research, 2025)
Background: Patient-Centered Care (PCC) is a key component of health services that emphasizes respect for patient dignity, provision of information, active participation, and collaboration in decision-making. Dr. M. Djamil General Hospital needs to evaluate the implementation of PCC from the patient’s perspective to identify service gaps and improve care quality. This study aimed to assess the implementation of PCC across four main dimensions: dignity, information provision, patient participation, and collaboration. Methods: This study employed a descriptive quantitative design with a cross-sectional approach, involving 353 inpatients selected through stratified random sampling. Data were collected from January to June 2024 using a structured questionnaire adapted from Harvey Picker’s PCC framework. Each dimension was measured with a Likert scale and analyzed descriptively. Results: Implementation of PCC was rated highly in terms of dignity by physicians (94.94%) and nurses (96.32%). Information provision received positive perceptions for physicians (75.92%) and nurses (77.34%), but lower for dietitians (57.79%) and pharmacists (57.79%). The participation dimension was rated lower for physicians (58.36%), dietitians (54.67%), and pharmacists (66.01%), while nurses received a comparatively better score (56.66%). Collaboration was perceived positively for physicians (54.96%) and nurses (58.07%). Conclusion: The implementation of PCC showed favorable results in dignity, information, and collaboration, while patient participation remained suboptimal. Strengthening effective communication and enhancing active involvement of all healthcare professionals, including pharmacists and dietitians, were essential to improve the quality of patient-centered care.